Bibliometrics and Visual Analysis of the Research Status and Trends of Breastfeeding in Turkey - Ucar, Tuba; Celik, Osman Tayyar; Baransel, Esra Sabanci; Barut, Sumeyye (Aves, 2023)
Objective: The long- and short-term benefits of breastfeeding for mothers and infants are known, and the number of studies on this subject is increasing daily. This study aimed to reveal current research trends, hotspots, and future frontiers in research on breastfeeding in Turkey. Materials and Methods: The most productive institutions, influential authors, the journals with the most publications by the authors, core research teams, and keywords in Turkey in the field of breastfeeding were analyzed using bibliometric methods. Additionally, breastfeeding-related articles published in the Web of Science Core Collection between 1980 and 2022 were scanned. The collected data were analyzed with the R Bibliometrix package program and VOSviewer. Results: It was determined that research on breastfeeding has accelerated since 2004, and the number of citations has increased with the number of publications. The fields of most productive writers in the area were found as social pediatrics, and the most influential institutions were Istanbul University and Hacettepe University. It was determined that there was no specialization in research on breastfeeding among authors distributed based on their productivity. The results also revealed the most influential articles and journals. The word analysis revealed that the breastfeeding literature in Turkey is sensitive to current developments, whereas the current status of breastfeeding, the factors affecting breastfeeding, and the effects of breastfeeding are the top areas of research. It was observed that maternal attachment and coronavirus disease-2019 (COVID-19) pandemic-related issues have been studied more in recent years. Conclusion: This bibliometric analysis contributes to understanding the current status and development of breastfeeding research in Turkey.
Keywords: Breastfeeding; bibliometrics; research; Turkey